The Intersection of Art and Technology: A Study on Generative AI and its Implications for Human Creativity - Hary Murcahyanto; Napat Chai; Siri Lek (Journal of Loomingulisus ja Innovatsioon, 2025)
The emergence of generative artificial intelligence (AI) has redefined the boundaries between artistic creation and computational design, prompting critical debates on the evolving nature of human creativity. The rapid advancement of AI tools capable of producing visual art, music, and literature challenges traditional notions of authorship, originality, and aesthetic value. This study aims to explore the intersection of art and technology by examining how generative AI transforms creative processes and influences artistic identity. A qualitative research design employing case studies and thematic analysis was utilized to investigate the experiences of 15 artists and designers who integrate AI-based tools, such as DALL·E, Midjourney, and ChatGPT, into their creative workflows. Data were collected through in-depth interviews, artifact analysis, and digital ethnography. The findings reveal that generative AI functions as both a collaborator and a disruptor expanding creative possibilities while raising ethical and philosophical questions about human agency in artmaking. Participants reported enhanced productivity, conceptual exploration, and aesthetic experimentation, yet also expressed concerns about the loss of emotional authenticity and authorship. The study concludes that generative AI represents a paradigm shift toward co-creative art, necessitating new frameworks for understanding creativity, ethics, and digital aesthetics in the post-human era.